A review to the association between schizophrenia and attachment (2018)
ABSTRACT: The theory of attachment as a spectrum in evolutionary psychology has shown its importance in interpersonal functioning and in the consolidation of personality traits, and also, this has aroused interest in research on how this factor influences psychopathology, since this will give more strength to the idea that early life has great weight for the consequences, dysfunctions and disorders in adulthood, as is the case of schizophrenia. Attachment is that affective bond that we establish with our most representative figures during childhood and that we become internal models of work and help to configure in us responses to separation, anguish and security (Crittenden, 2000). The classifications of attachment styles have been described by different authors from their main researchers such as Bowlby and Ainsworth (1979): secure, avoidant and ambivalent (Harder, 2014); and the disorganized as an opposite entity. On the other hand, schizophrenia has had a rapid evolution over the years since the psychiatric phenomenology began the search for explanations around it because thanks to this has been delimited the symptomatology, the biological etiology and the plans for treatment. On the contrary, schizophrenia continues with multiple causes and theories that make it a clinical mystery, since it does not provide a universality regarding its origin and course. This psychopathology is characterized by the appearance of positive and negative symptoms. The positive ones refer positive or productive symptoms reflect the appearance of phenomena that were not present in the past, these can be hallucinations, delusions, formal disorders of thought (incoherence and illogicality), extravagant behaviors and catatonia; while the negative or deficit symptoms reflect the loss of a previously acquired capacity or characteristic, such as language problems, affective flattening, apathy, anhedonia and abulia. With these categories, research has endowed a significant amount of ideas and new concepts that have allowed to approach the associations between schizophrenia as psychopathology and attachment as an early cause or risk factor and vulnerability to the acquisition of it.